Social Media is a Marketing Tool for MSMEs in Tegal Parang for Business Sustainability and Environmental Preservation - Indrajaya, Sonny; Setyaningrum, Retno Purwani; Nusaningrum, Dewi (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This research focuses on the role of social media in business development to realize MSME Marketing in Tegal Parang, Tegal Parang Village, Mampang Prapatan for business sustainability and environmental sustainability Method: This research uses a community service approach to achieve its objectives. This activity includes training sessions in the form of providing theory, examples, discussion forums and mentoring to improve social media skills. Practical Application: The results of this study are useful for members of the MSMEs and the community in developing product designs and marketing. Conclusion: This research underlines the importance of providing training to MSME members and the community which can improve product design and increase product sales volume. This has practical implications for increasing the volume of MSME products which has an impact on improving the welfare of MSME members.